2022
DOI: 10.1002/cctc.202200962
|View full text |Cite
|
Sign up to set email alerts
|

N‐Heterocyclic Carbene‐Based Zinc Complexes: Same Precursors for Different Lactide Ring‐Opening Polymerization Mechanisms.

Abstract: Two zinc complexes bearing NHC ligands were synthesized and fully characterized by NMR spectroscopy. Their behavior in the Ring-Opening Polymerization (ROP) of lactides was investigated under several conditions of reaction. They showed to be efficient initiators, producing polylactides with molecular weights depending on the cocatalysts. Microstructural analysis of poly(rac-LA) by 1 H NMR spectroscopy revealed a slightly enriched-heterotactic PLAs with P r values up to 0.66. Inspection of the kinetic parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 103 publications
1
6
0
Order By: Relevance
“…2 Thus, the Zn (II) ion, being economically viable, naturally available in abundance, and biocompatible, plays a substantial role in synthetic chemistry. [3][4][5][6] Unlike transition metals, zinc-catalyzed reactions are mechanistically distinct for specific reactions such as polymerization, [7][8][9] oxidative coupling reactions, [10][11][12] and dehydrocoupling of alcohols with silanes. [13][14][15] From the synthesis of the first organozinc compound-diethylzinc-from metallic zinc and ethyl iodide by Frankland et al to date, several potential applications of organo-zinc compounds have been reported, demonstrating the evolution of synthetic organic chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…2 Thus, the Zn (II) ion, being economically viable, naturally available in abundance, and biocompatible, plays a substantial role in synthetic chemistry. [3][4][5][6] Unlike transition metals, zinc-catalyzed reactions are mechanistically distinct for specific reactions such as polymerization, [7][8][9] oxidative coupling reactions, [10][11][12] and dehydrocoupling of alcohols with silanes. [13][14][15] From the synthesis of the first organozinc compound-diethylzinc-from metallic zinc and ethyl iodide by Frankland et al to date, several potential applications of organo-zinc compounds have been reported, demonstrating the evolution of synthetic organic chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Lately, our group reported zinc complexes supported by backbone-substituted N-heterocyclic carbene (NHC) ligands as active catalysts in the ROP of lactides, showing different types of mechanism in the presence of different initiators . The catalytic abilities of NHC-based zinc complexes have been extensively reviewed in the literature. Due to the similarity of the ring-opening polymerization processes of lactide and cyclic carbonates, in the present work we decided to extend the scope of this class of zinc complexes by employing one of them as a catalyst in the ring-opening polymerization of TMC and its alkyl-substituted congeners, purposely synthesized from CO 2 and 1,3-diols.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Alternatively, the direct insertion of NHC • HX precursors into metal sources, such as PdCl 2 or Ag 2 O, provides another convenient access to metal-NHC complexes (Scheme 1b). [5] Although NHCs generally act as robust ancillary ligands that strongly bind to metal centers, [6] miscellaneous reactions that hamper the formation of metal-NHC complexes or cause their degradation were identified over the years. [7] For instance, reductive elimination or displacement reactions involving carbene ligands were observed in a number of cases.…”
Section: Introductionmentioning
confidence: 99%